Oyster Farming, Temperature, and Plankton Influence the Dynamics of Pathogenic Vibrios in the Thau Lagoon - Lopez-Joven, Carmen; Rolland, Jean-Luc; Haffner, Philippe; Caro, Audrey; Roques, Cécile; Carré, Claire; Travers, Marie-Agnès; Abadie, Eric; Laabir, Mohamed; Bonnet, Delphine; Destoumieux-Garzón, Delphine (Frontiers in Microbiology, 2018)
Vibrio species have been associated with recurrent mass mortalities of juvenile oysters Crassostrea gigas threatening oyster farming worldwide. However, knowledge of the ecology of pathogens in affected oyster farming areas remains scarce. Specifically, there are no data regarding (i) the environmental reservoirs of Vibrio populations pathogenic to oysters, (ii) the environmental factors favoring their transmission, and (iii) the influence of oyster farming on the persistence of those pathogens. This knowledge gap limits our capacity to predict and mitigate disease occurrence. To address these issues, we monitored Vibrio species potentially pathogenic to C. gigas in 2013 and 2014 in the Thau Lagoon, a major oyster farming region in the coastal French Mediterranean. Sampling stations were chosen inside and outside oyster farms. Abundance and composition of phyto-, microzoo-, and mesozooplankton communities were measured monthly. The spatial and temporal dynamics of plankton and Vibrio species were compared, and positive correlations between plankton species and vibrios were verified by qPCR on isolated specimens of plankton. Vibrio crassostreae was present in the water column over both years, whereas Vibrio tasmaniensis was mostly found in 2013 and Vibrio aestuarianus was never detected. Moreover, V. tasmaniensis and V. crassostreae were found both as free-living or plankton-attached vibrios one month after spring mortalities of the oyster juveniles. Overall, V. crassostreae was associated with temperature and plankton composition, whereas V. tasmaniensis correlated with plankton composition only. The abundance of Vibrio species in the water column was similar inside and outside oyster farms, suggesting important spatial dispersion of pathogens in surrounding areas. Remarkably, a major increase in V. tasmaniensis and V. crassostreae was measured in the sediment of oyster farms during cold months. Thus, a winter reservoir of pathogenic vibrios could contribute to their ecology in this Mediterranean shellfish farming ecosystem.